Bias-minimized quantification of microRNA reveals widespread alternative processing and 3′ end modification. Issue 5 (3rd January 2019) - Kim, Haedong; Kim, Jimi; Kim, Kijun; Chang, Hyeshik; You, Kwontae; Kim, V Narry
Abstract: MicroRNAs (miRNAs) modulate diverse biological and pathological processes via post-transcriptional gene silencing. High-throughput small RNA sequencing (sRNA-seq) has been widely adopted to investigate the functions and regulatory mechanisms of miRNAs. However, accurate quantification of miRNAs has been limited owing to the severe ligation bias in conventional sRNA-seq methods. Here, we quantify miRNAs and their variants (known as isomiRs) by an improved sRNA-seq protocol, termed AQ-seq (accurate quantification by sequencing), that utilizes adapters with terminal degenerate sequences and a high concentration of polyethylene glycol (PEG), which minimize the ligation bias during library preparation. Measurement using AQ-seq allows us to correct the previously misannotated 5′ end usage and strand preference in public databases. Importantly, the analysis of 5′ terminal heterogeneity reveals widespread alternative processing events which have been underestimated. We also identify highly uridylated miRNAs originating from the 3p strands, indicating regulations mediated by terminal uridylyl transferases at the pre-miRNA stage. Taken together, our study reveals the complexity of the miRNA isoform landscape, allowing us to refine miRNA annotation and to advance our understanding of miRNA regulation. Furthermore, AQ-seq can be adopted to improve other ligation-based sequencing methods including crosslinking-immunoprecipitation-sequencing (CLIP-seq) and ribosome profiling (Ribo-seq).